Selection of Indonesia Cassava (Manihot esculenta Crantz) Genotype as Source of Î²-Carotene - DODY PRIADI; DJUMHAWAN RATMAN PERMANA; SRI ELIN DONA; SRI HARTATI; ENNY SUDARMONOWATI (Society for Indonesian Biodiversity, 2009)
Fourteen genotypes of Indonesia cassava (Manihot esculenta Crantz) of two generations were evaluated for Î²-carotene content. The Î²-carotene content of tubers and leaves were determined by spectrophotometry method. Other parameterssuch as water and ash contents were also evaluated. Results showed that Î²-carotene content of tubers of fourth generation(planted in 2006-2007) was higher than that of first generation (planted in 2002-2003), with the exception of Apuy, Iding andSarewen genotypes. Î²-carotene content of tubers was lower than that in their leaves of fourth generation plants and that there was no correlation between both organs in terms of Î²-carotene content of tubers and their leaves except for Tim-Tim 40 genotype. Î²-carotene content of tubers in several genotypes i.e. Kalbar III (1.13 ppm), Local Muneng (1.03 ppm), Tim-Tim 29 (1.61 ppm) was higher than 1 ppm, and the highest value was found in Tim-Tim 40 (16.83 ppm) which was significantly different (5%) with other genotypes. Meanwhile the lowest content was found in Sarewen genotype as it could not be detected. Water and ash contents of the tubers were between 54 and 69% and between 0.20 and 0.79% respectively. As Î²-carotene is the precursor of vitamin A, consuming high Î²-carotene tubers are sufficient for daily requirements of vitamin A, although further study is needed.Key words: cassava, Manihot esculenta, genotype, selection, Î²-carotene, tubers, leaves